Learning outcomes through role play by simulating real-life scenarios: English for Information Technology System (ITS) Students - Rosadi, Ariani; Setyawati, Gitalis (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This study aims to investigate learning outcomes through role-play with real-life scenario simulations in English lessons for Information Technology Systems (STI) students at Mbojo Bima University. This study applied a qualitative research method with a descriptive type. The data sampling technique used purposive sampling and the researcher intentionally selected students of first semester. The methods of qualitative data collection most commonly used are document study, observations, semi-structured interviews and focus group discussion. Then, the data was analyzed using the Miles and Huberman model which consisted of data reduction, data presentation and conclusion drawn. The conclusions of this study include students’ learning experiences and learning approach. Students' learning experience in this study involved applying real-life contexts, active participation, enhancing confidence, practicing specific grammatical structures and vocabulary related to the scenario. Then, in this research, PBL as a learning approach facilitated students’ opportunity to develop their critical thinking in order to connect students’ learning experiences in real-life with language competence and skill.